2016
DOI: 10.1523/jneurosci.3629-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Theta-Alpha Oscillations Bind the Hippocampus, Prefrontal Cortex, and Striatum during Recollection: Evidence from Simultaneous EEG–fMRI

Abstract: Recollection of contextual information represents the core of human recognition memory. It has been associated with theta (4 -8 Hz) power in electrophysiological recordings and, independently, with BOLD effects in a network including the hippocampus and frontal cortex. Although the notion of the hippocampus coordinating neocortical activity by synchronization in the theta range is common among theoretical models of recollection, direct evidence supporting this hypothesis is scarce. To address this apparent gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
84
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 59 publications
13
84
1
1
Order By: Relevance
“…While our EEG data do not allow conclusions about the precise neuronal sources, theta oscillations in general are suggested to play a major role in several cognitive functions including goal-directed behavior and memory processes by synchronizing neuronal activity across limbic, striatal and cortical nodes, probably reflecting the coordination of processing relevant information (Buzsáki and Draguhn, 2004; Düzel et al, 2010; Herweg et al, 2016). Since theta power did not directly relate to the integrity of SN/VTA or NAcc, and since there was no relationship to RTs in our current work, it is also plausible that it might more closely reflect reward processing in cortical brain regions such as the medial frontal cortex (Silvetti et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…While our EEG data do not allow conclusions about the precise neuronal sources, theta oscillations in general are suggested to play a major role in several cognitive functions including goal-directed behavior and memory processes by synchronizing neuronal activity across limbic, striatal and cortical nodes, probably reflecting the coordination of processing relevant information (Buzsáki and Draguhn, 2004; Düzel et al, 2010; Herweg et al, 2016). Since theta power did not directly relate to the integrity of SN/VTA or NAcc, and since there was no relationship to RTs in our current work, it is also plausible that it might more closely reflect reward processing in cortical brain regions such as the medial frontal cortex (Silvetti et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have suggested that low frequency synchronizations facilitate long-distance communication. For instance, theta synchrony has been reported to coordinate activity between regions, such as V4-FEF (Liebe et al, 2012), STR-HPC (DeCouteau et al, 2007), FEF-ACC (Babapoor-Farrokhan et al, 2017), PFC-HPC (Benchenane et al 2010), PFC-STR-HPC (Herweg et al, 2016), and LIP-TEO-V4-Pulvinar (Wang et al, 2012). In particular, one study found that as animals learned a procedural task, theta oscillations within STR and HPC became anti-phasic (DeCouteau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this role, mPFC both guides appropriate memory retrieval by using the context to resolve conflicting information, and participates in memory formation by resolving conflicts between pre-existing schemas and new events. This process of organizing multiple features into a single, coherent representation, integrating temporal and spatial information, involves theta-oscillations that functionally bind hippocampus and PFC (Herweg et al, 2016). If this system is not working well, (being a bit “unmoored” in time and space) it could create vulnerability to over-react to potential indicators of threat, enhancing vigilance, providing face validity for potential relevance to PTSD.…”
Section: A New Model: Deficient Context Processingmentioning
confidence: 99%